Online Digital Invitation (An Implementation with Go-Web) - Adi Ahmad; M. Arinal Ihsan; Hanis Novansyah; Muharratul Mina Rizky; Bakruddin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
This study aims to develop an online digital invitation service that can be used for all activities such as invitations to religious, family, and personal activities and in the application development process the Go Web framework is used. This study uses research with the Research and Development method. The product developed based on initial research is the Online Digital Invitation System. The test subjects in this development are expert subjects and students of STMIK Indonesia Banda Aceh as potential users of the product. This research was taken by random sampling technique, which consisted of 20 small-scale and 30 large-scale test people. The data collection technique was done by using a questionnaire. This questionnaire was conducted to assess the application developed from the completeness of the application and the material as well as the physical appearance of the application. Data analysis is descriptive quantitative and qualitative. Based on the results of research and discussion of research results to develop an Online Digital Invitation System, several stages of feasibility testing are needed, namely media expert tests, material expert tests and tests on respondents. Based on the results of research on small group trials, the Digital Online Invitation System was obtained. Most 90% stated that it was very feasible to use, and the results of research on large trials, most of the students, 96.67% stated that it was very feasible to use. With these results, it can be concluded that the Online Digital Invitation System is very feasible to use. Based on the conclusions from the results of the study, it is implied that the Online Digital Invitation System is very feasible to use, so that it becomes good input for users in making digital invitations both used through browsers and android.